Epigenetics-Associated Risk Reduction of Hematologic Neoplasms in a Nationwide Cohort Study: The Chemopreventive and Therapeutic Efficacy of Hydralazine - Yang, Bing-Heng; Lin, Wei-Zhi; Chiang, Yu-Ting; Chen, Yeu-Chin; Chung, Chi-Hsiang; Chien, Wu-Chien; Shiau, Chia-Yang (Frontiers in Oncology, 2022)
Background: Although several epigenetic drugs have been reported to have therapeutic efficacy for some hematologic neoplasms (HNs) in clinical trials, few achieved disease-free survival benefit. The traditional drug discovery pathway is costly and time-consuming, and thus, more effective strategies are required. We attempted to facilitate epigenetic drug repositioning for therapy of HNs by screening Human Epigenetic Drug Database (HEDD) in web, conducting bench work cytotoxicity test and retrospective nationwide cohort study prior to a clinical trial. Methods: Four FDA-approved epigenetic drugs with antitumor properties and completion of clinical phase II trials were selected from HEDD. Hydralazine (HDZ) and valproate (VAL) among the four were selected with higher cytotoxicity to HN cells, no matter whether carrying JAK2V617F mutation or not. Both of them were chosen for a cohort study using the Longitudinal Health Insurance Database (LHID) 2000-2015 (N = 1,936,512), a subset of National Health Insurance Research Database (NHIRD, N= 25.68 millions) in Taiwan. Results: In the initial cohort, HDZ or VAL exposure subjects (11,049) and matching reference subjects (44,196) were enrolled according to maximal daily consumption (300/2100 mg per day of HDZ/VAL). The HNs incidence in HDZ and VAL exposure groups reduced from 4.97% to 3.90% (P < .001) and 4.45% (P = .075), respectively. Further cohort study on HDZ at lower range of the WHO defined daily dose (< 34mg per day), HN incidence of HDZ exposure subjects (75,612) reduced from 5.01% to 4.16% ( P = 1.725×10 -18) compared to the reference subjects (302,448). Conclusions: Association of a chronically prescribed HDZ, even prescribed low dose, with reduction of overall incidence rate and in most subgroups of HN was observed in our study. Repositioning HDZ for HNs management may be feasible. This is the first nationwide cohort study of epigenetics-associated risk evaluation of overall HN in the existing literature, showing an effective method with a wider scope to inform contemporary clinical trials of epigenetic drugs in the future.